Evaluation of Physiological Parameters and Effectiveness of an Immobilization Protocol Using Etorphine, Azaperone, and Butorphanol in Free-Ranging Warthogs (Phacochoerus africanus) - Neiffer, Donald; Buss, Peter; Hewlett, Jennie; Hausler, Guy; Rossouw, Leana; Manamela, Tebogo; Grenus, Brittany; Thulson, Emily; Olea-Popelka, Francisco; Miller, Michele (Frontiers in Veterinary Science, 2019)
Twenty free-ranging warthogs (Phacochoerus africanus) in the Kruger National Park, South Africa, were immobilized with a combination of etorphine (0.039 ± 0.005 mg/kg) and azaperone (0.44 ± 0.06 mg/kg) administered intramuscularly by dart. Butorphanol (1 mg per mg etorphine) was administered intravenously at t=5 min. A standardized scoring system was used to record induction, immobilization and recovery characteristics. Physiological parameters were recorded at 5 min intervals and an arterial sample collected for blood gas analyses every 15 mins. At 45 mins after butorphanol administration, immobilization was partially reversed by administering naltrexone (40x etorphine dose in mg) intravenously. Overall, induction quality was good, with the mean time to safe handling 5.9 ± 1.4 mins. The majority of immobilization scores (54%) over the entire monitoring period (40 mins) were at level 3, consistent with a light plane in which some reflexes were still present but the animal could be safely handled. Overall mean heart rate was 94.7 ± 15.3 beats per min, mean respiratory rate was 14.7 ± 9.8 breaths per min, and the mean rectal temperature was 38.5 ± 1.0˚C. Significant hypoxia (overall mean oxygen arterial partial pressure 38.8 ± 8.4 mmHg), hypercapnia (mean carbon dioxide arterial partial pressure 63.3 ± 7.8 mmHg), and acidosis (mean pH 7.28 ± 0.04) were observed in immobilized warthogs. Following antagonist administration, warthogs were standing within 1.0 ± 0.4 mins, with the majority of recoveries scored as excellent. The drug combination proved to be effective in the immobilization of free-ranging warthogs with rapid induction and recovery, but with significant cardio-respiratory changes. Therefore, this drug combination may be useful when rapid immobilization and recovery are indicated, but should be used cautiously in compromised warthogs.